AB0260 Dynamic Serum Matrix Metalloproteinase-3 as A Diagnostic Biomarker of Erosive Disease and Radiographic Progression in Rheumatoid Arthritis. (10th June 2014) - Ma, J.-D.; Mo, Y.-Q.; Chen, L.-F.; Zheng, D.-H.; Zhu, L.-J.; Dai, L.
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic synovitis, resulting in joint destruction and disability. Matrix metalloproteinase (MMP) 3 plays essential role in the degradation of extracellular components and cartilage. Several studies reported that serum MMP-3 could predict progression of joint damage in RA. However, there were seldom reports about dynamic change of serum MMP-3 and its relationship with radiographic progression in RA. Objectives: To monitor serum MMP-3 and explore its correlation with radiographic progression in RA. Methods: Sixty-eight patients with active RA who fulfilled the 1987 revised criteria of ACR were recruited and were divided into erosive and non-erosive group according to 2013 EULAR definition of erosive disease in hand radiographs. All patients were followed up at regular interval (1, 3, 6, and 12 months). Serum MMP-3 was detected by ELISA and clinical data was collected simultaneously at baseline and each visit. X-ray assessment of hand/wrist was repeated at 12 month visit and radiographic progression was defined as the change of total Sharp score more than 0.5 from baseline to one year. Results: (1) Baseline serum MMP-3 in erosive RA patients (n=31, median 384 ng/ml, IQR 218–589 ng/ml) was significantly higher than that in non-erosive RA patients (n=37, median 204 ng/ml, IQR 91–338 ng/ml, P=0.004). Spearman's rank order correlation showed significant correlations between baseline serum MMP-3 with space narrow score (r=0.349), erosion score (r=0.397) or total Sharp score (r=0.371, all P<0.05). ROC curve analysis showed that the tradeoff value of baseline serum MMP-3 for distinguishing erosive disease in RA was 369ng/ml with sensitivity 55% and specificity 81% (AUC=0.706, 95%CI: 0.583–0.829, P=0.004). (2) Twenty-nine RA patients fulfilled 1 year follow-up and 31% (9/29) showed radiographic progression. Wilcoxon matched-samples rank sum test between baseline and each visit showed that serum MMP-3 significantly decreased after 3 months and Kaplan-Meier estimates showed median occurrence time of normal serum MMP-3 was 3 months in radiographic non-progression RA patients (95%CI: 1.3–4.7 months), while serum MMP-3 continued elevated throughout 12 months in radiographic progression RA patients (Fig.1 ). (3) According to the change of serum MMP-3 after 3 months follow-up, RA patients were divided into decreased group (serum MMP-3 became decreased or even to normal, n=19) and non-decreased group (serum MMP-3 elevated continually, n=10). The ratio of RA patients with radiographic progression was significantly higher in non-decreased group than that in decreased group (70% vs 11%, P=0.002). Single factor logistic regression analysis showed that continually elevated serum MMP-3 at follow-up was a significant predictor for radiographic progression in RA patients (P=0.003, OR=19.833, 95%CI of OR=2.7 to 145.67). Conclusions: Serum MMP-3 may be a helpful diagnostic biomarker of erosive disease and continually elevated serum MMP-3 may be a significant predictor for radiographic progression in RA. Acknowledgements: This work was supported by Chinese National Natural Science Research Grant (grant no. 81373183 and 81001334), Specialized Research Fund for the Doctoral Program of Higher Education (grant no.20130171110075) and Guangdong Natural Science Foundation (grant no.S2013010014396). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2434